Intervening on exercise and daylong movement for weight loss maintenance in older adults: A randomized, clinical trial. Issue 1 (21st December 2021) - Fanning, Jason; Rejeski, W. Jack; Leng, Iris; Barnett, Cheyenne; Lovato, James F.; Lyles, Mary F.; Nicklas, Barbara J.
Abstract: Objective: This study aimed to determine the impact of dietary weight loss (WL) plus aerobic exercise (EX) and a "move more, more often" approach to activity promotion (SitLess; SL) on WL and maintenance. Methods: Low‐active older adults (age 65‐86 years) with obesity were randomized to WL+EX, WL+SL, or WL+EX+SL. Participants received a social‐cognitive group‐mediated behavioral WL program for 6 months, followed by a 12‐month maintenance period. EX participants received guided walking exercise with the goal of walking 150 min/wk. SL attempted to achieve a step goal by moving frequently during the day. The primary outcome was body weight at 18 months, with secondary outcomes including weight regain from 6 to 18 months and objectively assessed physical activity and sedentary behavior at each time point. Results: All groups demonstrated significant WL over 6 months ( p < 0.001), with no group differences. Groups that received SL improved total activity time ( p ≤ 0.05), and those who received EX improved moderate‐to‐vigorous activity time ( p = 0.003). Over the 12‐month follow‐up period, those who received WL+EX demonstrated greater weight regain (5.2 kg; 95% CI: 3.5‐6.9) relative to WL+SL (2.4 kg; 95% CI: 0.8‐4.0). Conclusions: Pairing dietary WL with a recommendation to accumulate physical activity contributed to similar WL and less weight regain compared with traditional aerobic exercise.